Pengaruh Beberapa Faktor Terhadap Produktivitas Kerja Karyawan (Studi pada: LPK Istibank di Surakarta) - putri, Siti Rahmawati Ramadhani Putri, Drs.Kusdiyanto M.Si (2016)
The purpose of this research to analyze the influence of some factors of worker produktivity in LPK Istibank Surakarta. And independent variable are work ability, fee, spirituality and dependent variabel is produktivity. This researc also tries to reveal the meaningfulness of the model in explaining produktivity. This research hopefully will be able to understanding regarding to produktivity and can be used as reference for future researched. The hypothesis in this research it is believed that there is an influence positive and significant among variable work ability, fee, and spirituality of the produktivity in the LPK Istibank Surakarta. And fee variabel have influence positive and significant to produktivity than another variabel independent. The population of this research it is all of the worker in the LPK Istibank Surakarta there is 32 worker. This research used validity test, reliability test, normality, multikolinieritas, heteroskedastisitas, and multiple regression test,Ttest, F test, and determinasi test). This research have found some finding. The first finding is work ability, and fee influence positive and significant on worker produktivity. But variable spirituality influence negative and not significant on worker spirituality. And second fiding it is fee variable influence dominant positive and significant on worker produktivity. This research give the recommend for management LPK Istibank Surakarta in order that in the take wisdom about fee like in the wisdom now or upgrade the fee because it is make produkitvity the worker become better. Keywords : Produktivity, Work Ability, Fee, Spirituality.